Effect of potassium on the mechanisms of biomass pyrolysis studied using complementary analytical techniques - Le Brech, Yann; Ghislain, Thierry; Leclerc, Sébastien; Bouroukba, Mohammed; Delmotte, Luc; Brosse, Nicolas; Snape, Colin; Chaimbault, Patrick; Dufour, Anthony (Wiley, 2016)
Complementary analytical methods have been used to study the effect of potassium on the pyrolysis mechanisms of cellulose and lignocellulosic biomasses. Thermogravimetry, calorimetry, high-temperature 1H NMR spectroscopy (in situ and real-time analysis of the fluid phase formed during pyrolysis), and water extraction of quenched char followed by size-exclusion chromatography coupled with mass spectrometry have been combined. Potassium impregnated in cellulose suppresses the formation of anhydrosugars, reduces the formation of mobile protons, and gives rise to a mainly exothermic signal. The evolution of mobile protons formed from K-impregnated cellulose has a very similar pattern to the evolution of the mass loss rate. This methodology has been also applied to analyze miscanthus, demineralized miscanthus, miscanthus re-impregnated with potassium after demineralization, raw oak, and Douglas fir. Hydrogen mobility and transfer are of high importance in the mechanisms of biomass pyrolysis.